Effect of simultaneous electrical and mechanical stressing on porosity of Ti3C2Tx MXene films. (10th March 2023) - Sharp, Logan C; Al-Mamun, Nahid Sultan; Wetherington, Maxwell; Haque, Aman
Abstract: MXenes are atomically layered carbides and nitrides of transition metals that have potential for micro-devices applications in energy storage, conversion, and transport. This emerging family of materials is typically studied as nanosheets or ultra-thin films, for which the internal defects are mostly nanoscale flake-flake interface separation type. However, micro-devices applications would require thicker films, which exhibit very high density of microscale pores. Electrical conductivity of thicker MXenes is significantly lower than nanosheets, and the physics of defect size and density control are also different and less understood. Current art is to perform high temperature annealing to improve the electrical conductivity, which can structurally alter or degrade MXene. The key contribution of this study is a room-temperature annealing process that exploits the synergy between electrical pulses and compressive mechanical loading. Experimental results indicate over a 90% increase in electrical conductivity, which reflects a decrease in void size and density. In the absence of compressive loading, the same process resulted in a conductivity increase of approximately 75%. Analytical spectroscopy and microscopy indicated that the proposed multi-stimuli process kept the MXene composition intact while significantly decreasing the void size and density.